Spectroscopic and astrometric radial velocities: hyades as a benchmark - Leão, Izan de Castro; Ludwig, Hans-Günter (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. We study the accuracy of spectroscopic radial velocities (RVs) by comparing spectroscopic and astrometric RVs for stars of the Hyades open cluster. W